Moderating effect of Innovation on the Relationship between Customer Focus Strategy and Performance of Manufacturing Firms in Kenya - Kiprotich, Evans; Gachunga, Hazel; Bonke, Ronald (International Journal of Strategic Management, 2023)
Purpose: The manufacturing sector is experiencing a major problem of stiff competition emanating from illicit and illegal trade. The study aims at providing insights on relationship between customer focus strategy and performance of manufacturing firms in Kenya to achieve competitiveness. The objective was to establish the moderating effect of innovation on the relationship between customer focus strategy and performance of manufacturing. Methodology: The study was anchored on Porter's competitive strategy typology. The study adopted the explanatory research design. The study targeted population of 766 procurement managers from manufacturing firms in Kenya. The Yamane's formula was used to compute a sample size of 264 procurement managers. Stratified, simple random and purposive sampling was used to select respondents. Questionnaire was used to collect primary data. The data was coded and entered in the computer for analysis using the Statistical Package for Social Sciences. Quantitative data was analyzed using Process Macro. Results: Results indicated that customer focus strategy (Î²= -.346, p=.000) had negative and significant relationship with performance of manufacturing firms. Innovation (Î²=.822, p=.000) were positively significantly related with performance of manufacturing firms. The interaction between customer focus strategy and innovation was significant (Î²=.373, p=.000), indicating that the effect of customer focus strategy on performance of manufacturing firms depended on innovation strategy. The study concluded that customer focus strategy had a negative significant relationship with performance of manufacturing firms. The study concluded that innovation moderate the relationship between customer focus strategy and performance of manufacturing firms in Kenya. Unique Contribution to Theory, Policy and Practice: The manufacturing firms pursuing focus competitive strategy should strive to identify customers whose needs and wants are not met by differentiators and cost leaders and offer services and products not offered by their competitors in order to remain competitive in the market place. In order to gain from this strategy, the manufacturing firms should pay attention to the market segment which is sustainable so as to avoid the dangers encountered when pursuing focus competitive strategy such as focusing on a segment that is pursuing innovation.